International Marketing Policy: A Discussion of the Standardization Construct and its Relevance for Corporate Policy - Walters, Peter G. P. (Journal of International Business Studies, 1986)
A fundamental question in international marketing concerns the desirability and feasibility of standardizing marketing programs and procedures internationally. The primary objective of this paper is to present an overview and evaluation of the standardization debate. Central issues of interest include a discussion of the standardization construct and an evaluation of the evidence regarding corporate implementation of standardization strategies.